Government expenditure variables and economic growth in Zambia - Sekele, Ezekiel Chisenga (Research of GSB, 2018)
The government sector forms a significant part of the economy. As such, it is important to examine the impact of government activities on the economy. This study investigates the impact of several components of government expenditure on economic growth between 2001Q1 and 2014Q4 using the vector error correction model. The study found that only expenditure on transport and gross fixed capital formation had a significant positive impact on economic growth in the short-run. In the long-run, only expenditures on transport and education had a significant impact on economic growth. However, expenditure on health has a negative, although insignificant, impact on economic growth. This result may be due to the heavy concentration of health expenditure on disease treatment rather than disease preventive measures. Spending on defense has no significant impact on economic growth. Expenditure on agriculture was found to have no significant impact on economic growth both in the short- and long-run, partly due to a heavy concentration of expenditure on price-distorting agriculture input- and output-price support programs. The findings of the study suggest that there is need to focus expenditure on increasing agricultural productivity, improving the quality of education, improving road infrastructure and expanding disease prevention measures.